Pembelajaran Tahsin Qur’an Pada Madrasah Ibtidaiyah: Analisis Pembiasaan Sebelum Memulai Pembelajaran - Dawi, M. Nuh (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the implementation of the routine tahsin Qur’an program before learning in MIS Kuba and the students' responses to the habituation process. The habituation activities include reading repetition, tajwid improvement, and enhancing students' spiritual character, such as discipline and love for the Qur’an. The results show that the habituation before tahsin Qur’an learning has a significant positive impact, with most students showing improvement in reading the Qur’an with correct tajwid. Students' responses were very positive, with many feeling helped and more confident in reading the Qur’an. However, some students still struggled with pronouncing certain letters. This study contributes to the development of tahsin Qur’an learning methods, especially in emphasizing the importance of habituation before starting more in-depth tahsin learning.